Revisiting sovereign bond spreads’ determinants in the EMU - Afonso, António (2016)
We study the determinants of 10-year sovereign bond yield spreads of 11 EMU member states, covering the lifetime of the euro, up until the end of 2014. Panel and SUR analyses coupled with qualitative variables show that the pricing of European debt has not been static across time and EMU countries, and market participants became increasingly aware of macro- economic and fiscal fundamentals.